ANALYSIS OF THE INTRINSIC ELEMENTS OF A SHORT STORY “LELAKI YANG TUBUHNYA HABIS DIMAKAN IKAN-IKAN KECIL” BY MASHDAR ZAINAL - Duril, Sefrury; Khaerunaila, Muh. Fajar; Kezia, Triadinda Cias; Putra, La Ode; Mutmainnah, Mutmainnah (Seshiski: Southeast Journal of Language and Literary Studies, 2024)
Short story is a part of literary genres, which is a fiction, that most of it relies on fantasy stories such as fairy tale. Short stories have elements that are divided into two which are intrinsic elements and extrinsic elements. This study aims to analyse the intrinsic elements in the short story titled "Lelaki yang Tubuhnya Dimakan Ikan-Ikan Kecil" by Ahmad Mashdar Zainal. Employing a structural approach with qualitative methods, this research focuses on the identification, description, and interpretation of the intrinsic elements present in the short story. The data processing involves reading and noting, as well as identifying the theme, plot, characterization, setting, point of view, mandate and language style. Furthermore, this study includes sentences as data evidence derived from "Lelaki yang Tubuhnya Dimakan Ikan-Ikan Kecil" to analyse and interpret its content while providing an in-depth review of the short story. The analysis results indicate that intrinsic elements exist within this short story, encompassing theme, characterization, plot, setting, point of view, stylistic devices, and a clearly conveyed moral message. By analysing the intrinsic elements within this short story, it is hoped that readers will gain motivation and a deeper understanding.